Mechanical Characteristics of Epoxy Composite With Rice Husk Charcoal Filling Material - Maryudi, Maryudi; Hanum, Farrah Fadhillah; Loundi Vidinda , Oktaza; Dwi Anto , Arif (Universitas Ahmad Dahlan, 2023)
Advancements in science and innovation in the modern world have led to a growing demand for materials in the production of goods. The utilization of materials in the manufacturing process has been reduced. This is due to the heaviness, costliness, susceptibility to corrosion, and complex assembly systems of metal materials compared to natural fibers. One of the materials currently under development is composites. Composites are a mixture of at least two materials that vary in shape, chemical structure, and are non-disintegrating. The aim of this study is to explore the fabrication and influence of rice husk volume fraction in epoxy composites, as well as to test their tensile strength and composite characteristics. The methodology involves preparing the raw materials (rice husk charcoal, epoxy resin, epoxy hardener, and silicon spray), rice husk charcoal preparation, epoxy production from resin and epoxy hardener, and composite manufacturing with volume fractions of 10%, 20%, and 30% following ASTM D-638 standards. The testing of composite characteristics through tensile tests yields varying tensile strengths. The highest tensile strength is found in composites with a volume fraction of 10%, while the lowest tensile strength is found in composites with a volume fraction of 30%.